Ambiete de tanque-rede aumenta as interações agressivas e o estresse social na tilápia-do-Nilo - Boscolo, Camila Nomura Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The social position (dominance or submission) in Nile tilapia is signalize through visual sound, and chemical information. Such signals can be reduced in cages, where the high rate of water renewal may dilute the chemical information environment. In addition, the cages do not have removable substrate, which also acts as a reducing of aggressive interactions for Nile tilapia. Thus, we tested the hypothesis that the concomitant absence of signals of social position in cages environment increases aggressive interactions and consequently the social stress in territorial fish. Groups of three male Nile tilapia (GIFT) were maintained in aquaria containing networks (imitating cages) and were tested in five treatments: 1. Substrate presence / without water renewal (Control 1). 2. Substrate presence / without water renewal - no network (Control 2). 3. Substrate presence/ plus water renewal. 4. Substrate absence / plus water renewal. 5. Substrate absence / without water renewal. The animals were grouped by two days, during which it was recorded (15 min / day) the frequency of aggressive interactions. We assess the social stability by means of reversals in social position (rank) of individuals and levels of Testosterone (T) and 11 - cetotestosterona (KT). We use cortisol and liver glycogen as an indicator of stress. The frequency of aggressive interactions and cortisol levels were higher in the treatments without removable substrate. Moreover, we observed that there was a higher rank reversal of the treatments with water renewal. Testosterone levels were higher in the treatments without removable substrate. KT was higher in treatments without damage to social cues. Thus, we conclude that the absence of indicators of social position arising from the cages environment increases aggressive interactions and social stress in Nile tilapia. Furthermore, we observed that the indicators of social position ...

A posição social (dominância ou submissão) na tilápia-do-nilo é sinalizada por meio de informações visuais, sonoras e químicas. Tais sinalizações podem ser reduzidas em ambiente de tanque-rede, onde a elevada taxa de renovação de água pode “diluir” as informações químicas. Além disso, os tanques-rede não possuem substrato removível, que também atua como um redutor das interações agressivas para a tilápia-do-nilo. Assim, testamos a hipótese de que a ausência concomitante de sinalizadores da posição social em ambiente de tanque-rede aumenta as interações agressivas e, consequentemente o estresse social em peixes territoriais. Grupos de três machos de tilápia-do-nilo (GIFT) foram mantidos em aquários contendo redes (imitando tanques-rede) e foram testados em cinco tratamentos: 1. Com substrato/sem renovação de água (Controle 1). 2. Com substrato/sem renovação de água - sem rede (Controle 2). 3. Com substrato/com renovação de água. 4. Sem substrato/com renovação de água. 5. Sem substrato/sem renovação de água. Os animais foram agrupados por dois dias, nos quais foi registrada (15 min/dia) a frequência de interações agressivas. Avaliamos a estabilidade social por meio das reversões na posição social (rank) dos indivíduos e dos níveis de Testosterona (T) e 11-cetotestosterona (KT). Utilizamos cortisol e glicogênio hepático como indicador de estresse. A frequência de interações agressivas e os níveis de cortisol foram maiores nos tratamentos sem substrato removível. Além disso, observamos que houve maior reversão do rank nos tratamentos com renovação de água. Os níveis de testosterona foram mais elevados nos tratamentos sem substrato removível. Já a KT foi maior nos tratamentos sem prejuízo dos sinais sociais. Assim, concluímos que a ausência de indicadores da posição social decorrente do ambiente do tanque-rede aumenta ...
Keywords: Peixe - Comportamento agressivo; Tilapia (Peixe); Tilápia-do-Nilo; Androgenos; Substratos; Fishes